Kinematic Performance Analysis and Dimensional Optimization for 2PUS-PU Parallel Mechanism - Linxian Che; Jian Yi; Bing He; Xuedong Lin (Jixie chuandong)
The 1T2R 2PUS-PU parallel mechanism with one suitable constrained branch has no unwanted parasitic motion occurred in the constraint directions，then reducing efficiently the control difficulty. Based on the topological characteristic analysis of mechanism，its equations of displacement and orientation，velocity，and acceleration analysis are derived by means of the vector method. With the aid of the singularity of Jacobi matrix，the possible singular configurations of mechanism are investigated. The orientation of end-effector output axis is depicted by using the azimuth and tilt angles. Introducing the evaluation indices for motion/force transmission performance of mechanism，the definitions and calculation methods of regular transmission orientational workspace （RTOW） are given. A constrained optimization model is constructed to formulate the design problem of dimensional parameters on the maximizing radius of RTOW，and particle swarm optimization and differential evolution algorithm are adopted to solve this problem. A case of dimensional optimization design is given to indicate that the proposed model and algorithm are effective and feasible.